Comparison of open versus endovascular surgical treatment of abdominal aortic aneurysm - Kischkel Sabine (Current Directions in Biomedical Engineering, 2020)
Abdominal aortic aneurysm (AAA) is a common condition of increasing prevalence, particularly among older men. An AAA is defined as a permanent dilation of the abdominal aorta, with a diameter greater than 30 mm or a diameter greater than 50% of the aortic diameter at the level of the diaphragm. As the size of the aneurysm increases, so does the risk of rupture. Therefore, prophylactic repair with insertion of a prosthetic graft is offered. Since 1951 traditional open aneurysm repair (OAR) was reported and minimally invasive endovascular repair (EVAR) was first reported in 1986. Data from four randomized controlled trials (EVAR-1, DREAM, OVER, ACE) for abdominal aortic aneurysm, which enrolled almost 3000 patients, in a period from 1999 to 2008, were summarized. In addition, registry databases on the treatment of AAA of average 4000 patients per year, based from 2015 to 2018 of the German Institute for Vascular Medicine Healthcare Research of the German Society for Vascular Surgery and Vascular Medicine, were compared. The EVAR procedure for AAA showed a lower risk of perioperative mortality but was associated with a higher cardiovascular and aneurysm-related complication rate. In particular, patients aged 80 years or older benefited from EVAR since the 30-day mortality of patients receiving OAR was higher. In mid-term and long-term follow-up there were no differences in survival after endovascular and open aortic repair. Overall, it depends on the respective underlying disease and anatomy which of the two approaches is to be preferred. In conclusion, both treatment options can be considered as equal and can be offered to patients.